(untitled) (Revista Argentina de Musicología, 2018)
The purpose of this work is to revise the notion of musical sensibility examining two current cases in the urban West-central region of Brasil. The first one considers the Evangelical religious system and that of the Candomblé; the second concerns social inequal1ties and the hip-hop practice in marginalized urban areas. The focus of interest is centered on the limits of the theoretical productivity of the notion of musical sensibility, as a useful tool in the understanding of connections among music, religion, politics and power, allowing establishing affinities with specific world visions in collision and with new emergent forms of political culture which makes explicit the social conflict.